EXPLORING THE ECONOMIC LINK BETWEEN FINANCIAL RISK STRATEGIES AND LONG-TERM SUSTAINABILITY IN THE BANKING INDUSTRY - Kusumawati, Rahayu; Yusuf Agustian, Mochamad Ferdy; Rosyalita, Dita (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research explores the relationship between financial risk strategies and long-term sustainability in the banking sector. It aims to examine how banks manage financial risks and their impact on long-term viability, focusing on credit, market, and operational risks. Using a library-based methodology, the study reviews relevant literature, including books, journals, and reports, to analyze risk management frameworks and sustainability practices. The findings indicate that while traditional risk strategies like Value at Risk are essential, integrating sustainability practices—such as CSR and ESG—improves a bank’s resilience and long-term performance. The study concludes that banks adopting comprehensive risk strategies aligned with sustainability are better positioned for long-term success.